Fibrous Dysplasia of the Maxilla: Diagnostic Reliability of the Study Image. Literature Review - Fusconi, Massimo; Conte, Michela; Pagliarella, Martina; De Vincentiis, Chiara; De Virgilio, Armando; Benincasa, Anna Teresa; Alessi, Simone; Gallo, Andrea (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective Fibrous dysplasia (FD) is a benign bone disorder in facial bones. This study evaluates the possibility of diagnosing fibrous dysplasia on imaging alone, without biopsy of the lesion, which is often burdensome for the patient.Materials and Methods The authors bring their experience of four cases of bone lesions of the maxillofacial region and present a review of published studies. The imaging techniques evaluated are computed tomography (CT) and magnetic resonance imaging (MRI) with and without contrast.Results The literature review demonstrates that it is impossible to make diagnosis of fibrous dysplasia exclusively by imaging. Radiographic images often show a ground-glass appearance, which is characteristic but not pathognomonic of fibrous dysplasia.Conclusion Although CT and MRI images may in many cases suggest a diagnosis of fibrous dysplasia, histological examination or follow-up imaging should follow.
Keywords: fibrous dysplasia; radiology; Paget; ossifying fibroma; osteosarcoma